STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA (PENDIDIK DAN TENAGA KEPENDIDIKAN) DI MADRASAH IBTIDAIYAH PADA ERA REVOLUSI INDUSTRI 4.0 - Dukan Jauhari Faruq; Abd Muis Tabrani Tabrani (LPPM IAD Probolinggo, 2026)
The rapid advancement of the Industrial Revolution 4.0 has compelled Madrasah Ibtidaiyah (Islamic primary schools) to enhance the quality of human resources among educators and educational staff in response to the digital transformation of education. This study seeks to examine human resource development strategies implemented in Madrasah Ibtidaiyah within the context of the Industrial Revolution 4.0, as well as to explore the challenges arising from their implementation. A qualitative descriptive design was adopted, with data gathered through interviews, classroom observations, and document analysis. The participants of this study consisted of the school principal, teachers, and educational staff at MIS Mambaul Hidayah Gumukmas. The results reveal that human resource development is carried out through technology-oriented internal training, strengthened teacher collaboration via Teacher Working Groups (KKG), ongoing professional development, benchmarking initiatives, and the digitalization of madrasah management. Despite existing constraints, the findings underscore that well-planned and collaborative human resource development strategies are essential in improving the professionalism of educators and educational staff in Madrasah Ibtidaiyah.